Plasma cell dyscrasia: monoclonal gammopathies, AL-amyloidosis, multiple myeloma Clinical case study - V. V. Cherepanova; M. A. Kurysheva; S. V. Odintsova (Онкогематология, 2023)
This study was performed in real clinical practice settings. Our paper describes two case studies which show the difficulty of differential diagnosis of monoclonal gammopathies, multiple myeloma associated with AL-amyloidosis and primary AL-amyloidosis.